REVIEW OF EFFECT OF STRYCHNOS NUXVOMICA ON VARIOUS DISEASES OCCURRING IN PERSON BORN WITH ASHWINI NAKSHATRA - Pratibha B. Visave; Deepali D. Choudhari (International Journal of Applied Ayurved Research, 2016)
Introduction: Ayurved and astrology are proven to be an Indian heritage. They both are established with scientific base. Now a day they have got worldwide acceptance. Aim of both the sciences is mainly concerned with human health i.e. physical and mental status.It is seen that there is a massive impact of planets, status of planets at the time of birth in the horoscope as well as constellations in our day to day life. Indian astrology has stated 27 Nakshatras (Constellations). Constellation means a group of specific stars in the sky. Each Nakshatra is indicated with one particular plant species known as Aaradhya vriksha (worshipped plant). In the same way Strychnos Nuxvomica is the plant stated for Ashwini Nakshatra. Aims and objectives:-To know the significance behind the indication of Strychnos Nuxvomica in Ashwini Nakshatra is the aim of this study. Person belonging to Ashwini Nakshatra has probability of getting specific diseases according to status of planets and Ashwini Nakshatra. Mode of action of Strychnos Nuxvomica in those particular diseases will be discussed in detail so as to get correlation between indication of Strychnos Nuxvomica and diseases occurring in Ashwini Nakshatra.